Estudo de fibras de folhas de abacaxis (gênero Ananas) e sua utilização em compósitos biodegradáveis com matriz de poli(ácido lático) (PLA) - Sena Neto, Alfredo Rodrigues de (Universidade Federal de São Carlos, 2014)
In this work natural fibers from new pineapple varieties were studied aiming at their application as mechanical reinforcement for green polymer composites. Eighteen varieties of pineapple leave fibers (PALFs) were then characterized in terms of their morphology, structural arrangement (cellulose crystallinity index (Ic) and microfibril angle), chemical composition (extractives, lignin, holocellulose, cellulose and hemicellulose contents), mechanical properties (tensile strength, elastic modulus and fracture strain) and thermal stability. The studied PALFs had low microfibril angles and high Ic. Their elastic modulus, tensile strength and degradation temperature onset ranged between 15GPa-86GPa, 212MPa-1309MPa, 240°C 272ºC, respectively. All these parameters enabled to nominate the eighteen PALFs as suitable reinforcements for polymers. Close relationships between cellulose, holocellulose and Ic values, and thermal and mechanical properties of PALFs were found out, what provided guidelines for direct selection and/or to support a genetic improvement program of the Ananas genus. An example of such a methodology was presented in this work. The fiber from the pineapple variety called "Potyra" was selected to produce biodegradable composites with poly(lactic acid) (PLA) through injection molding. The Potyra fibers were before hand treated with alkaline solution in order to improve their interfacial compatibility with PLA. The treated Potyra fibers-reinforced composite exhibited an increased elastic modulus from 1,9 GPa to 3,5GPa, tensile strength from 58,8 to 69,6MPa, and notched impact strength from 2,57kJ/m2 to 4,26kJ/m2 in comparison to the pure PLA matrix. The HDT of the PLA was also incremented by 10% due to the fiber incorporation. These findings confirmed the promising potential of Potyra fibers as reinforcements in green composite technologies.
Study of pineapples leafs fibers (Ananas genus) and their use as reinforcements for biodegradable poly(latic acid) (PLA)-based composites
Keywords: Compósitos poliméricos; Fibras vegetais; Abacaxi; Polímeros biodegradáveis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA